Features of nanoparticle composite-enhanced CO2 foam-flooding systems for low-permeability reservoirs - Liu, Yong; Zhao, Fajun; Niu, Ruixia; Cao, Sheng; Liu, Lei; Song, Yarui (Frontiers in Energy Research, 2023)
In this paper, under the reservoir geological conditions of Shu 16 block in Yushu forest field, an enhanced foam flooding system with nanoparticles and polymer is selected. The system is mainly composed of anionic foaming agent CQS-1 and nonionic surfactant FH-1. To screen the 17 foams by evaluating the foaming volume and foam half-life of the foam, Warning-blender method and dynamic foam analysis method was used. The nanoparticles were selected by examining the concentration of foam, the ratio of main agent to auxiliary agent, and the dosage of foam stabilizer. And the selected system analyzed the microstructure and rheological properties. The adaptability of the reservoir to its temperature resistance, salt tolerance and adsorption resistance has been determined, so that it can provide some support for the field application of CO2 foam flooding.